2022
DOI: 10.5217/ir.2021.00089
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of inflammatory bowel disease in Singapore

Abstract: Interestingly, epidemiological studies also revealed that children of parents that had migrated from region with low IBD prevalence in Asia, and currently residing in developed countries, exhibit similar high incidence of IBD compared to offspring of non-immigrants, suggesting how disease risk could be more influence by earlier life exposure to environmental antigens. 6 Over the past two decades, while IBD case in Asia, including Singapore, has risen significantly, it is still considered relatively lower compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In Asia, our projections indicate that IBD incidence will continue to rise until reaching a plateau by 2030. Additionally, high-income countries in Asia are already in the Compounding Prevalence stage and are transitioning to Prevalence Equilibrium [ 49 , 56 , 63 ]. Although the incidence has plateaued, the annual number of cases in high-income countries is expected to decrease, potentially due to demographic shifts resulting from declining fertility rates in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, our projections indicate that IBD incidence will continue to rise until reaching a plateau by 2030. Additionally, high-income countries in Asia are already in the Compounding Prevalence stage and are transitioning to Prevalence Equilibrium [ 49 , 56 , 63 ]. Although the incidence has plateaued, the annual number of cases in high-income countries is expected to decrease, potentially due to demographic shifts resulting from declining fertility rates in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…IMIDs can be classified into three groups based on the affected organs. Inflammatory bowel diseases (IBD: Crohn's disease and ulcerative colitis), inflammatory arthritides (rheumatoid arthritis and ankylosing spondylitis), and psoriasis are IMIDs that mainly affect the gut, joints, and skin, respectively (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Studies have shown that each IMID is associated with a higher risk of depression and anxiety in the general population with effect sizes similar to that of T2DM (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of inflammatory bowel disease (IBD) is increasing rapidly in many Asian countries [1][2][3]. Because IBD is an immune-mediated chronic disease, the majority of patients require lifelong treatment with immunosuppressive agents, such as thiopurines, methotrexate, biologics, and small molecule agents [4].…”
Section: Introductionmentioning
confidence: 99%